Policy Study on The Implementation of Islamic Education at The Secondary Level and Islamic Higher Education of 2006 - 2020 - Sapdi, Rohmat Mulyana; Masykhur, Anis; Anwar, Chairul; Sada, Heru Juabdin (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research elaborates on the results of Islamic education policy research with the object of reviewing regulations on the administration of secondary and tertiary education issued in the 2006-2020 period. Based on the main task and function of the Minister of Religion contained in Presidential Regulation Number 83 of 2015 is to administer the government in the field of religion. The scope of authority for administering education is also in the area of religion, as emphasized in Government Regulation No. 55 of 2007. Since Law no. 20 of 2003 concerning the National Education System, there has been a fundamental change in implementing Islamic education. The Minister of Religious Affairs has a wider mandate in the education sector that extends to non-religious fields. This is marked by the widespread establishment of academic madrasas at the secondary level and institutional transformation to UIN at the higher education level. The Regulation of the Minister of Religious Affairs No. 90 of 2013 concerning the Implementation of Madrasas Education and The Regulation of the Minister of Religious Affairs No. 15 of 2014 concerning the changes in the Form of Religious Higher Education Institutions confirms the basis for changes in the orientation of the implementation of secondary and higher education. At the Madrasah Aliyah level, the development of non-religious study programs is growing faster than religious study programs. At the Islamic higher education level, students with a religious education background are smaller than those with a general education background.